Intensifying Insecurities: The impact of climate change on vulnerability to human trafficking in the Indian Sundarbans - Molinari, Nicole (Anti-Trafficking Review, 2017)
Despite an enormous amount of attention paid to the factors that shape vulnerability to human trafficking, such as poverty and a lack of economic opportunity, the debate of evidence for what enables these factors to exist in the first place is relatively less explored. Presently, discussions of the relationship between climate change and human insecurity have been marginal to broader debates about vulnerability to trafficking. This paper argues that this signifies a gap in our understanding of the underlying drivers that push individuals and communities into situations where vulnerability to trafficking amplifies, but also that increase the pull of risky migration pathways and exploitative work situations. This paper proceeds by examining and problematising dominant conceptualisations of vulnerability in human trafficking and climate change discourses. Next, it presents a case study of the Sundarbans region of India to highlight how climate change impacts compound and exacerbate the same factors that shape vulnerability to human trafficking—including environmental degradation, loss of livelihood, destitution, and forced migration. Lastly, it argues for enhanced attention to climate change-related insecurity as evidence of vulnerability to trafficking and outlines what such insights can bring to anti-trafficking efforts.